Glass ionomer cement as an occlusive barrier in Class III furcation defect - Rameshwari Singhal (Wolters Kluwer Medknow Publications, 2011)
Predicting the prognosis of molars that have experienced furcation invasion, is often a frustrating experience to the dental clinician and disappointing report to the patient involved. Although multiple treatment modalities have been attempted to retain teeth with severe furcation invasion, clinical success has not been predictable. A case report involving the use of glass ionomer cement (GIC) as an occlusive barrier in the management of Class III furcation defect involving mandibular first molar is presented. A literature review on the subject matter was conducted using Medline, Google search engines, and manual library search. GIC restoration of Class III furcation invasion gives a satisfactory result. Surgical and nonsurgical treatment options are available for the management of the condition. GIC as an occlusive barrier in Class III furcation invasion is an economical and less invasive treatment option. It also makes home care easy for the patient.